Knowledge Management System for Cultural Patrimony Including Voice Interface for Knowledge Acquisition - Château, Stefan du; Boulanger, Danielle; Mercier-Laurent, Eunika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
This paper presents our research on a first part of hybrid Knowledge Management System for Cultural Patrimony - knowledge acquisition and ontological indexing. It describes our experimentation of a voice interface for the on field inventory of cultural heritage. This acquisition system includes signal processing, natural language techniques and knowledge modeling tools for future retrieval. We discuss the first results and raise some challenges of future work.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 38-47